2005
DOI: 10.1186/1471-2407-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Rare mutations predisposing to familial adenomatous polyposis in Greek FAP patients

Abstract: BackgroundFamilial Adenomatous Polyposis (FAP) is caused by germline mutations in the APC (Adenomatous Polyposis Coli) gene. The vast majority of APC mutations are point mutations or small insertions / deletions which lead to truncated protein products. Splicing mutations or gross genomic rearrangements are less common inactivating events of the APC gene.MethodsIn the current study genomic DNA or RNA from ten unrelated FAP suspected patients was examined for germline mutations in the APC gene. Family history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The large APC gene rearrangements were identified in 26 patients, and 12 of them were deletions of the whole APC gene (Aretz et al 2005). In Greek patients, only one large rearrangement in 25 studied families was detected (Mihalatos et al 2005), while in another study in Belgium, 4 large rearrangements were revealed in 27 examined FAP families, and 3 of them were deletions of the whole APC gene (Michils et al 2005). In the German and Belgian groups, the percentage of large rearrangements was almost equal (15%), but in the Greek group it was 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The large APC gene rearrangements were identified in 26 patients, and 12 of them were deletions of the whole APC gene (Aretz et al 2005). In Greek patients, only one large rearrangement in 25 studied families was detected (Mihalatos et al 2005), while in another study in Belgium, 4 large rearrangements were revealed in 27 examined FAP families, and 3 of them were deletions of the whole APC gene (Michils et al 2005). In the German and Belgian groups, the percentage of large rearrangements was almost equal (15%), but in the Greek group it was 4%.…”
Section: Discussionmentioning
confidence: 99%
“…The three nonsense mutations, one missense (p.Ile1307Lys) mutation and the other polymorphism (p.Thr1493Thr) were published before. Two of them (p.Ser1315Stop, p.Ile1307Lys) are characteristic of the Ashkenazi population [28][29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Linkage analysis to markers on chromosome 5q, protein tr uncation testing, direct sequencing, conformation-sensitive gel electrophoresis, and single-strand, conformation-sensitive gel electrophoresis all have accuracies 70%-90% [30] . Splice site defects or gross genomic alterations may have been underestimated by the older testing methods and require cDNA screening and gene rearrangement testing [31] . Genetic risk assessment should precede the initiation of regular endoscopic screening [32] .…”
Section: Discussionmentioning
confidence: 99%